MODEL PEMBELAJARAN PSIKOLOGI PENDIDIKAN PADA MAHASISWA TUNANETRA DI FAKULTAS TARBIYAH DAN ILMU KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA - Riski Nursafitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This qualitative research aims to understand the learning experience of visually impaired students in attending regular lectures. Through in-depth interviews and participatory observation, it was found that visually impaired students face various challenges, visual-based material delivery, and reading, as well as interaction challenges with lecturers and peers. However, they also show good adaptation and have effective learning strategies, so it takes the theory of reward, punishment and repetition to make children more imaginative and intellectual to achieve learning success. The media used is multimedia, because in the learning process must use media that supports and especially children with disabilities use Braille media because this media is very effective in order to be able to read and interpret the learning that is taught. Keywords: visually impaired students,methods, models